Економіко-математичне моделювання фіскального стимулювання розвитку смарт-промисловості - Турлакова, C.С.; Резніков, Р.Б.; Балабанов, С.В. (Вісник економічної науки України, 2023)
Дослідження зосереджено на аналізі сучасних економіко-математичних моделей фіскального стимулювання розвитку смарт-промисловості. Основна увага приділяється систематизації існуючих підходів, виявленню їх недоліків та визначенню потенційних напрямків для їх вдосконалення. Адаптація існуючих моделей до специфіки національної економіки України, а також врахування сучасних викликів глобалізації та цифрової трансформації виступає ключовим аспектом дослідження. Предметом дослідження виступають економіко-математичні моделі, які застосовуються для аналізу та стимулювання розвитку смарт-промисловості. В рамках дослідження проведено аналіз існуючих економіко-математичних моделей фіскального стимулювання, оцінка їх сильних та слабких сторін. Виявлено основні чинники, що впливають на розвиток смарт-промисловості, та розробка концептуальної моделі фінансового стимулювання для подальшого розвитку. Розроблено рекомендації щодо покращення фінансового забезпечення смарт-промисловості в Україні. Результати дослідження вказують на необхідність адаптації більшості існуючих моделей до умов сучасної української економіки. Виявлено ключові напрямки для покращення цих моделей, зокрема через врахування специфіки національного розвитку та залучення інноваційних факторів. Розроблено рекомендації, які можуть бути використані для покращення фіскального стимулювання розвитку смарт-промисловості. Застосування економіко-математичних моделей виступає важливим інструментом для аналізу впливу фіскального стимулювання на смарт-промисловість. Це дозволяє адаптувати існуючі підходи до специфіки національної економіки та врахувати особливості сучасних умов. В цілому, дослідження сприяє розумінню того, як економіко-математичне моделювання може бути використане для підтримки та стимулювання розвитку смарт-промисловості, забезпечуючи тим самим стійке економічне зростання та інноваційний розвиток. Objective: The study focuses on analyzing contemporary economic-mathematical models of fiscal stimulation for the development of smart industry. Primary attention is dedicated to systematizing existing approaches, identifying their shortcomings, and determining potential directions for their improvement. Adapting existing models to the specifics of the national economy of Ukraine, as well as considering the contemporary challenges of globalization and digital transformation, represents a key aspect of the research. Tasks: Several key tasks have been defined within the study. First and foremost is the analysis of existing economic-mathematical models of fiscal stimulation, evaluating their strengths and weaknesses. The second task is to identify the main factors influencing the development of smart industry, and to develop a conceptual model of financial stimulation for its further advancement. The third task involves developing recommendations for improving the financial support of smart industry in Ukraine. Subject: The subject of the study encompasses economic-mathematical models applied for analyzing and stimulating the development of smart industry. The study conducts a detailed analysis of various approaches, their application, and effectiveness. Methods: The research employs an analytical literature review, comparative analysis, as well as the application of economic-mathematical modeling. These methods allow for an evaluation of the current state of affairs in the field and the development of well-founded recommendations for improving existing approaches. Main Results: The findings of the study indicate the necessity to adapt the majority of existing models to the conditions of the contemporary Ukrainian economy. Key directions for improving these models have been identified, particularly through considering the specifics of national development and incorporating innovative factors. Practical recommendations have been developed, which can be utilized to enhance fiscal stimulation for the development of smart industry. Conclusions: The application of economic-mathematical models serves as a vital tool for analyzing the impact of fiscal stimulation on smart industry. It enables the adaptation of existing approaches to the specifics of the national economy and consideration of the peculiarities of contemporary conditions. Overall, the research contributes to understanding how economic-mathematical modeling can be used to support and stimulate the development of smart industry, thereby ensuring sustainable economic growth and innovative development.